New insight on the Xq28 association with systemic sclerosis. Issue 12 (26th February 2013) - Carmona, F David; Cénit, M Carmen; Diaz-Gallo, Lina-Marcela; Broen, Jasper C A; Simeón, Carmen P; Carreira, Patricia E; Callejas-Rubio, José-Luis; Fonollosa, Vicente; López-Longo, Francisco J; González-Gay, Miguel A; Hunzelmann, Nicolas; Riemekasten, Gabriela; et al.
Abstract : Objective: To evaluate whether the systemic sclerosis (SSc)-associated IRAK1 non-synonymous single-nucleotide polymorphism rs1059702 is responsible for the Xq28 association with SSc or whether there are other independent signals in the nearby methyl-CpG-binding protein 2 gene ( MECP2 ). Methods: We analysed a total of 3065 women with SSc and 2630 unaffected controls from five independent Caucasian cohorts. Four tag single-nucleotide polymorphisms of MECP2 (rs3027935, rs17435, rs5987201 and rs5945175) and the IRAK1 variant rs1059702 were genotyped using TaqMan predesigned assays. A meta-analysis including all cohorts was performed to test the overall effect of these Xq28 polymorphisms on SSc. Results: IRAK1 rs1059702 and MECP2 rs17435 were associated specifically with diffuse cutaneous SSc (PFDR =4.12×10 −3, OR=1.27, 95% CI 1.09 to 1.47, and PFDR =5.26×10 −4, OR=1.30, 95% CI 1.14 to 1.48, respectively), but conditional logistic regression analysis showed that the association of IRAK1 rs1059702 with this subtype was explained by that of MECP2 rs17435. On the other hand, IRAK1 rs1059702 was consistently associated with presence of pulmonary fibrosis (PF), because statistical significance was observed when comparing SSc patients PF+ versus controls (PFDR =0.039, OR=1.30, 95% CI 1.07 to 1.58) and SSc patients PF+ versus SSc patients PF− (p=0.025, OR=1.26, 95% CI 1.03 to 1.55). Conclusions: Our data clearly suggest the existence of two independent signals within the Xq28 region, one located in IRAK1 related to PF and another in MECP2 related to diffuse cutaneous SSc, indicating that both genes may have an impact on the clinical outcome of the disease.